1991
DOI: 10.1111/j.1600-0536.1991.tb01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the quenching phenomenon in delayed contact hypersensitivity reactions

Abstract: Studies in guinea pig and man have shown that eugenol can quench non-specifically contact urticarial responses, whereas limonene seems largely ineffective. In a comprehensive series of studies, there was little evidence of quenching of delayed contact hypersensitivity reactions to cinnamic aldehyde or citral, including in 'pre-quenched' material supplied by a perfume/flavour company, and in a similar mixture prepared in this laboratory, in the guinea pig model. In addition, there was no evidence of the quenchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Let us consider the outcome of the published guinea pig work (12,13) in more detail. Studies were conducted in OECD standard assays (14), which encompass both adjuvant and non-adjuvant tests, as well as in non-standard methods.…”
Section: Quenching: the Induction Of Skin Sensitizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Let us consider the outcome of the published guinea pig work (12,13) in more detail. Studies were conducted in OECD standard assays (14), which encompass both adjuvant and non-adjuvant tests, as well as in non-standard methods.…”
Section: Quenching: the Induction Of Skin Sensitizationmentioning
confidence: 99%
“…In the work of the Strasbourg group, using a guinea pig predictive test, the effect of limonene on the induction of skin sensitization to citral, unfortunately, was not examined (8). This variable was investigated thoroughly, however, in an extensive series of investigations using a variety of guinea pig models (12,13). The outcome of these studies can be summarized quite simply -no quenching effect could be demonstrated.…”
Section: Quenching: the Induction Of Skin Sensitizationmentioning
confidence: 99%
See 3 more Smart Citations